Applying Possessive Pronoun in Writing Sentences: Exploring Students’ Ability and Problems in a Mixed Method Study - Syahdan Syahdan; Eka Utami Putri (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2020)
The purpose of this research was to find out the students' ability in applying Possessive pronoun in writing sentences and the problems encounter it. This mixed method study employs an explanatory design to reveals it. 53 students out of 105 students from1st semester EFL students from one reputable University in Pekanbaru, Indonesia, were invited to this study. These 53 students were selected using simple random sampling and enrolled for an essay test and interview to see the students' ability and explaining the problems. The data analysis using SPSS showed that the average score of students was 52.98. Meanwhile for the median is 48, the mode is 20. The score of Standard Deviation is 27.93, Variance is 780.25, and Range is 84. Z-Score was found 41.5%, which is means higher than average and 58.5% while, students' ability was indicated below the average. It showed that the students were low ability in applying possessive pronoun in writing sentences. The study also found the common problems, i.e., (1) students still mixed up between possessive pronoun and possessive adjectives. (2) students used the wrong pattern in using a possessive pronoun. (3) students did not understand clearly about a possessive pronoun, (4) experiencing difficulties in learning possessive pronoun.